Respon Beberapa Varietas Padi Terhadap Serangan Fusarium fujikuroi Penyebab Penyakit Bakanae - Darnetty, Darnetty; Sulyanti, Eri (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2017)
Fusarium fujikuroi is the cause of bakanae disease in rice plants. Level of bakanae disease attack on some rice cultivation land in West Sumatra, especially in Padang Pariaman district is quite high. One effort to suppress the development of F. fujikuroi is by planting resistant varieties. In this study, 15 rice varieties originating Sumatera Barat were used to be tested for their response to F. fujikuroi attack. The purpose of this study was to obtain the varieties with the low attack rate of F. fujikuroi. Parameters observed were number of dead seeds, number of dead seedlings, number of stunted seedlings, number of seeds showing symptoms of Bakanae and total infected seeds. The results of the study indicated that symptoms of F. fujikuroi attack varied which were dead seeds, stunting seedlings, dead seedslings and bakanae. The response of rice varieties to F. fujikuroi attack was different with characterized by different levels of infection rates. Low infection rates were found in Pessel varieties (2.0%), Batang sahalai (15.5%), Cisokan (17.0%), and Batang Lembang (20%). Other varieties showed a high percentage of F. fujikuroi attacks ranging from 20% to 54.5%.